Cryptosporidium suis and Cryptosporidium scrofarum in Eurasian wild boars (Sus scrofa) in Central Europe - Němejc, Karel; Sak, Bohumil; Květoňová, Dana; Hanzal, Vladimír; Janiszewski, Paweł; Forejtek, Pavel; Rajský, Dušan; Ravaszová, Petra; McEvoy, John; Kváč, Martin (Veterinary parasitology, 2013)
From 2011 to 2012, to identify Cryptosporidium spp. occurrence in Eurasian wild boars (Sus scrofa) 29 randomly selected localities (both forest areas and enclosures) across the Central European countries of Austria, the Czech Republic, Poland, and the Slovak Republic were investigated. Cryptosporidium oocysts were microscopicaly detected in 11 out of 460 faecal samples examined using aniline-carbol-methyl violet staining. Sixty-one Cryptosporidium infections, including the 11 infections that were detected by microscopy, were detected using genus- or species-specific nested PCR amplification of SSU rDNA. This represents a 5.5 fold greater sensitivity for PCR relative to microscopy. Combining genus- and species-specific PCR tools significantly changes the perspective on the occurrence of Cryptosporidium spp. in wild boars. While RFLP and direct sequencing of genus specific PCR-amplified products revealed 56 C. suis (20) and C. scrofarum (36) monoinfections and only 5 mixed infections of these species, species-specific molecular tools showed 44 monoinfections and 17 mixed infections with these species. PCR analysis of the gp60 gene did not reveal any other Cryptosporidium infections. Similar to domestic pigs, C. scrofarum was detected as a dominant species infecting adult Eurasian wild boars (Sus scrofa). Cryptosporidium infected wild boars did not show signs of clinical disease. This report is perhaps the most comprehensive survey of cryptosporidial infection in wild boars.
Keywords: Feces; Cryptosporidium scrofarum; Eurasian wild boar; Cryptosporidium; Cryptosporidiosis; Europe; Cryptosporidium suis; Evropa; Sus scrofa; SSU; Swine Diseases; PCR; nemoci prasat; Swine; zvířata; feces; Species Specificity; prasata; druhová specificita; Central Europe; kryptosporidióza; Animals